Impact of calcium peroxide dosage on the control of nutrients release from sediment in the anoxic landscape water - Yi Wang; Wen-Huai Wang; Xin-Xin Lu; Lin-Lin Feng; Fu-Rong Xue; Lu-Qin Sun (Environmental Science and Pollution Research, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Two new benzophenones from endohydric moss Polytrichum Commune - Xu-Hong Duan; Jian-Cheng Zhao; Lin Li; Lin Pei; Pei He; Rong Wang (Natural Product Research, 2019)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Proteomic responses to ocean acidification of the marine diazotroph Trichodesmium under iron-replete and iron-limited conditions - Futing Zhang; Haizheng Hong; Sven A. Kranz; Rong Shen; Wenfang Lin; Dalin Shi (Photosynthesis Research, 2019)

Genetic dissection of stalk lodging-related traits using an IBM Syn10 DH population in maize across three environments (Zea mays L.) - Yanling Zhang; Tianhu Liang; Min Chen; Yinchao Zhang; Tao Wang; Haijian Lin; Tingzhao Rong; Chaoying Zou; Peng Liu; Michael Lee; Guangtang Pan; Yaou Shen; et al. (Molecular Genetics and Genomics, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Evaluation of Whole Blood Trace Element Levels in Chinese Children with Autism Spectrum Disorder - Ling-ling Wu; Shan-shan Mao; Xu Lin; Rong-wang Yang; Zhi-wei Zhu (Biological Trace Element Research, 2019)

Salinity effects on the 2014 warm “Blob” in the Northeast Pacific - Hai Zhi; Pengfei Lin; Rong-Hua Zhang; Fei Chai; Hailong Liu (Acta Oceanologica Sinica, 2019)

First report of Dickeya fangzhongdai causing soft rot disease of Welsh onion in Taiwan - Wei-An Tsai; Pei-Rong Lin; Chien-Jui Huang (Journal of Plant Pathology, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Phytochemical composition and larvicidal activity of essential oils from herbal plants - Hsiang-Ting Huang; Chien-Chung Lin; Tai-Chih Kuo; Shiang-Jiuun Chen; Rong-Nan Huang (Planta, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

A special issue to mark the 90th Anniversary of College of Life Sciences, Zhejiang University - Jin-rong Peng; Kun-liang Guan; De-yuan Hong; Xin-hua Lin; Huan-ming Yang; Yu-xian Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Interannual Salinity Variability in the Tropical Pacific in CMIP5 Simulations - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Peng Yu (Advances in Atmospheric Sciences, 2019)

Environmental changes in the north‐east Sunda region over the last 40 000 years - Chuanxiu Luo; Simon Haberle; Zhuo Zheng; Rong Xiang; Chixin Chen; Gang Lin; Kumar Sazal (Journal of Quaternary Science, 2019)
Pollen and spores from 110 samples from sediment core NS07‐25 from the Nansha Trough in the South China Sea (SCS) were analysed with a particular focus on reconstructing vegetation and climate change and identifying the sources of palynomorphs on the Sunda Shelf during the Last Glacial Maximum (LGM). Palynomorph sources were identified using the Near Analysis function in ArcGIS with 62 data points of the pollen in surface sediment samples from the southern SCS. The results showed that during the LGM, pollen and spores came from the exposed Sundaland, whereas before and after the LGM, pollen and spores came from Borneo. Changes in vegetation and climate were inferred from pollen percentages, concentrations and influx and indicated that during the LGM, ferns, lowland rainforests, upper montane rainforests and lower montane forests were present on the north‐east part of the exposed Sunda Shelf but not over the entire Sunda Shelf. Climate during the LGM was cooler than it is today, but humidity was not substantially lower. During the LGM, grasses and shrubs did not cover the southern continental shelf of the SCS, possibly because they were located in the Intertropical Convergence Zone.

Over-expression of 5-HT6 Receptor and Activated Jab-1/p-c-Jun Play Important Roles in Pilocarpine-Induced Seizures and Learning-Memory Impairment - Changyun Liu; Yuxing Wen; Huapin Huang; Wanhui Lin; Mingzhu Huang; Rong Lin; Ying Ma (Journal of Molecular Neuroscience, 2019)

A CkDREB1 gene isolated from Caragana korshinskii Kom. enhances Arabidopsis drought and cold tolerance - Ziyi Zhang; Qi Yang; Chunlin Zhang; Lili Wei; Rong Yue; Guojing Li; Xiaofei Lin; Ruigang Wang (Brazilian Journal of Botany, 2019)

Electrode array and data density effects in 3D induced polarization tomography and applications for mineral exploration - Gang Zhang; Qing-Tian Lü; Pin-Rong Lin; Gui-Bin Zhang (Arabian Journal of Geosciences, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Polyphenol Removal from Sugarcane Juice by Using Magnetic Chitosan Composite Microparticles - Xing-quan Liang; Song-lin Fan; Jia-xing Zhang; Xiao-rong Song (Sugar Tech, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Blood Levels of Trace Elements in Children with Attention-Deficit Hyperactivity Disorder: Results from a Case-Control Study - Rongwang Yang; Yanyi Zhang; Weijia Gao; Nannan Lin; Rong Li; Zhengyan Zhao (Biological Trace Element Research, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)